PENGEMBANGAN PANDUAN PRAKTIKUM DI SMA NEGERI NIBUNG - Iis kusmiati; Destien Atmi Arisaandy; Nopa Nopiyanti (Nusantara Hasana Journal, 2025)
This study aims to determine the feasibility of the student practicum guide. This study uses the Research & Development (R&D) method with the Borg & Gall development model consisting of 10 stages, but modified into 5 stages. The data analysis technique uses quantitative descriptive and qualitative descriptive data obtained from validation by language experts, material experts, media experts, student and teacher readability tests. The validation results obtained a value of 84% from language experts, 73% from material experts, 80% from media experts, 92.25% from student readability tests and 92% from teacher readability tests. Based on these values, the resulting guide is declared feasible and can be used in SMA Negeri Nibung.